Philosophy for Children ed educazione emotiva. Un bilancio critico - Ariele Niccoli (Firenze University Press, 2020)
Philosophy for Children aims, among other things, to educate emotions through enhancing «caring thinking». The goal of this paper is to critically assess the Lipman-Sharp's theory of the emotions. It's firstly shown that P4C approach to emotion education rests on a theory that identifies emotions and evaluative judgments, then it's argued that it brings about an overintellectualization of the emotions. To conclude, it is suggested that P4C would benefit from theories of emotions that recognize a greater role to the body.